Bioprospecção do potencial antimicrobiano, antiparasitário e antitumoral de metabólitos secundários produzidos por fungos do gênero Aspergillus Spp. - Calado, Juliana Cristina Pereira [UNIFESP] (2018)
Filamentous fungi produce a wide variety of secondary metabolites that have a significant impact on society. Some metabolites are exploited by their activity as antibiotics and drugs; others are involved in diseases, in the interaction of fungi with plants and animals. In this context, the objective of this work was to obtain biologically active secondary metabolites produced by fungi isolated from the composting of the Fundação Zoológico de São Paulo (FPZSP). In this study, 71 organic extracts were used, 60 filamentous fungi and 11 yeasts. Of the 71 analyzed samples 25 presented antimicrobial activity in disc diffusion assays, and 23 samples showed activity against Staphylococcus aureus, 15 against Bacillus cereus and only one sample (I75) showed activity against Escherichia coli and Pseudomonas aeruginosa. The minimum inhibitory concentration (MIC) values were determined by microdilution in broth. Four of these samples had good antimicrobial activity (MIC 62.5 μg / mL) and 7 showed moderate activity (100500 μg / mL). Four samples showed antitumor activity with selectivity varying from 1.8 to 7.5 times. The best results were obtained for the activity against Leishmania (Leishmania) amazonensis. In the tests of leishmanicidal activity against the promastigote forms, 12 samples presented IC50 values equal to or less than 5 μg / mL, of which 3 showed good selectivity against the parasite in relation to the murine fibroblast lineage (values ranging from 5 to 50 times). Similar results for leishmanicidal activity against amastigote forms were observed in two of these extracts (I06 and I75). The I06 extract induced cell death by mitochondrial apoptosis and ROS production in the promastigote forms of L. (L.) amazonensis. The therapeutic potential of the organic extract of isolate I06 in cutaneous leishmaniasis model was also evaluated. BALB / c mice infected with L. (L.) amazonensis and treated with I06 extract showed a significant reduction in the lesion size in the paw as well as the parasite load. No signs of hepatic or renal toxicity were observed from histological analyzes and evaluation of serum levels of some biochemical markers. For the identification of the fungal species used in this study, partial sequencing of the intergenic region (STI) of ribosomal DNA and a region of the calmodulin gene was performed. All isolates with some biological activity belong to different strains of Aspergillus fumigatus. Thus, this dataset strongly suggests that a molecule or set of organic extract molecules from secondary metabolites of A. fumigatus (isolated I06) has leishmanicidal activity with high selectivity and low toxicity, thus presenting great potential for therapeutic use.